(untitled) (Journal of Advanced Geospatial Science & Technology, 2026)
The aim of this study is to apply a GIS-based approach to identify suitable areas for cultivating sea grapes (Caulerpa lentillifera) in Sabah. Specifically, the objectives are to assign weights to the factors influencing site suitability and to pinpoint potential cultivation zones. Key environmental variables considered include sea surface temperature, salinity, water depth, chlorophyll concentration, and UV light. Data for these criteria were sourced from NOAA, GEBCO, and other open-source databases. The Ranking Weighting method was used to establish the relative importance of each factor, followed by a Weighted Overlay Analysis (WOA) in GIS to produce a suitability map for sea grape cultivation in Semporna, Sabah. Results show that large areas around Semporna provide ideal conditions for sea grape farming, with high suitability indicated in green on the map. Among the factors assessed, salinity emerged as the most critical, while sea surface temperature had the least influence. The findings were further validated by expert input. The novelty of this study lies in it being the first comprehensive GIS-based assessment of sea grape cultivation potential in Sabah. While previous aquaculture research in the region has focused largely on other marine species or relied on isolated environmental parameters, this study integrates multiple environmental datasets within a spatially explicit framework to holistically evaluate site suitability. By combining remote sensing data, ranking-based weighting, and GIS overlay techniques, the research not only fills a critical knowledge gap but also establishes a replicable model for aquaculture site selection in Sabah’s tropical marine environments. Overall, the study demonstrates the effectiveness of GIS in identifying potential aquaculture sites for sea grape cultivation in Sabah. The resulting suitability map can serve as a strategic decision-support tool for the Sabah government and stakeholders in expanding sustainable sea grape cultivation.